Immunocyte-derived extracellular vesicles in osteoimmunology: mechanisms, disease contexts, and translational prospects - Yang, Lixuan; Li, Ning; Xu, Hao; Chen, Jinman; Liang, Qianqian (Frontiers in Immunology, 2025)
Bone remodeling disorders such as osteoporosis, rheumatoid arthritis, and periodontitis highlight the clinical significance of osteoimmune communication. Osteoimmunology has emerged as a key interdisciplinary field elucidating the dynamic interplay between the immune and skeletal systems, with extracellular vesicles (EVs) recognized as nanosized mediators that transport proteins, lipids, and RNAs to regulate bone remodeling. Immunocyte-derived EVs modulate osteoblast and osteoclast activity through macrophage polarization, Treg-associated CD73/adenosine signaling, Th17/Treg balance, and B cell–bone interactions, exerting dual effects by promoting bone formation under physiological conditions while amplifying inflammation and bone resorption in osteoporosis, rheumatoid arthritis, and periodontitis. Bidirectional communication between bone marrow stromal cell–derived EVs and immune cells further highlights the complexity of EV-mediated regulation in bone microenvironments. Moreover, engineering approaches such as cargo loading, surface modification, and biomaterial integration are rapidly advancing the therapeutic application of EVs in bone diseases. Despite these advances, challenges remain in EV standardization, scalable production, and clinical translation, underscoring that immunocyte-derived EVs represent both pathogenic mediators and promising therapeutic agents, with future studies required to resolve mechanistic complexity and optimize their clinical utility. Engineered EVs enable targeted modulation of CD73–adenosine, NF-κB, HIF-1α, and PI3K/AKT axes, offering bone-targeting delivery and immune-instructive biomaterials as converging strategies. These insights highlight immunocyte-derived EVs as both biomarkers and therapeutic candidates in bone disorders, and underscore the need for standardized approaches to advance their clinical utility in osteoimmunology.